Application of an inherent safety index to define the level of chemical risk: Case study in a research laboratory of a university center - Barrantes-Guzmán, Joel (2022)
The inherent safety methodology (IS) makes an analysis to try to avoid or eliminate hazards both in industries and in experimental laboratories by the evaluation of chemical risk. This methodology contemplates the adequate operation either in optimal or extreme working conditions, including physicochemical and toxicological parameters to ensure the reliability of the chemical process and to obtain an inherent safety index as a result. In this investigation, a total of 22 laboratory practices were evaluated with 76 chemical reagents with the aim of defining the level of chemical risk of a research laboratory manual of a university center, by applying an inherent safety risk index for the prevention of risks to human health and the environment. The result was an inherent safety index for the experimental chemical of 19 for the practice “Determination of oxygen, nitrogen, carbon monoxide, carbon dioxide and methane by gas chromatography”, this being the maximum core of chemical risk in the laboratory. The value obtained is very close to the theoretical inherent safety value (24), thus it is considered a risky practice.